QUEER CRIMINOLOGY - Buist, Carrie L.; Lenning, Emily ([S.l.] : ROUTLEDGE, 2022)
This book surveys the growing field of Queer Criminology. It reflects on its origins, reviews its foundational research and scholarship and offers suggestions for future directions. Moreover, this book emphasizes the importance of Queer Criminology in the field and the need to move LGBTQ+ issues from the margins to the center of criminological research. Core content includes: Contested definitions of and conceptual frameworks for Queer Criminology The criminalization of queerness and gender identity in historical and contemporary context The relationship between LGBTQ+ communities and law enforcement The impact of legislation and court decisions on LGBTQ+ communities The experiences of queer victims and offenders under correctional supervision This revised and updated edition includes new developments in theory and research, further coverage of international issues and a new chapter on victimization and offending. It is essential reading for those engaged with queer, critical, and feminist criminologies, gender studies, diversity, and criminal justice.
OCLC-licensed vendor bibliographic record.
Keywords: Sexual minorities; Criminology; Criminal justice, Administration of; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Gay Studies